The development of an adolescent smoking cessation intervention—an Intervention Mapping approach to planning - Dalum, Peter (Oxford University Press, 2012)
The objective of this project was to develop a theory- and evidence-based adolescent smoking cessation intervention using both new and existing materials. We used the Intervention Mapping framework for planning health promotion programmes. Based on a needs assessment, we identified important and changeable determinants of cessation behaviour, specified change objectives for the intervention programme, selected theoretical change methods for accomplishing intervention objectives and finally operationalized change methods into practical intervention strategies. We found that guided practice, modelling, self-monitoring, coping planning, consciousness raising, dramatic relief and decisional balance were suitable methods for adolescent smoking cessation. We selected behavioural journalism, guided practice and Motivational Interviewing as strategies in our intervention. Intervention Mapping helped us to develop as systematic adolescent smoking cessation intervention with a clear link between behavioural goals, theoretical methods, practical strategies and materials and with a strong focus on implementation and recruitment. This paper does not present evaluation data.